2015
DOI: 10.1093/ntr/ntv088
|View full text |Cite
|
Sign up to set email alerts
|

A Social Network Family-Focused Intervention to Promote Smoking Cessation in Chinese and Vietnamese American Male Smokers: A Feasibility Study

Abstract: Introduction: Smoking prevalence is high among limited English-proficient Chinese and Vietnamese American men, who are frequently unmotivated to quit and who underutilize smoking cessation resources. This study applied lay health worker outreach to leverage peer and family networks to promote smoking cessation among these men. Methods: We integrated qualitative formative research findings and Social Network Theory to develop a social-network family-focused intervention. In a pilot single-group trial, 15 lay he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 45 publications
(47 reference statements)
1
48
0
Order By: Relevance
“…Another trial in China indicated that a family‐assisted, motivational interviewing intervention (4 sessions) had higher rates of past‐week smoker abstinence at 6 months than an individual‐based intervention . A social‐network, family‐assisted intervention (2 group sessions and 2 follow‐up calls) demonstrated that Chinese and Vietnamese American smokers had a 30‐day abstinence rate of 24% at 3 months . Our study is consistent with these findings, indicating that engaging a household member with small group sessions may boost smoking‐cessation efforts and may improve elimination of household nonsmoker exposure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another trial in China indicated that a family‐assisted, motivational interviewing intervention (4 sessions) had higher rates of past‐week smoker abstinence at 6 months than an individual‐based intervention . A social‐network, family‐assisted intervention (2 group sessions and 2 follow‐up calls) demonstrated that Chinese and Vietnamese American smokers had a 30‐day abstinence rate of 24% at 3 months . Our study is consistent with these findings, indicating that engaging a household member with small group sessions may boost smoking‐cessation efforts and may improve elimination of household nonsmoker exposure.…”
Section: Discussionsupporting
confidence: 85%
“…Knowledge about secondhand smoke harms may not be enough, as demonstrated with the Health Belief Model, and future interventions could tailor actions toward more precontemplative smokers and might integrate more social support based on Social Network Theory . For example, a social‐network, family‐focused intervention leverages relationships across pairs recruited for group sessions to take actions based on the smokers' readiness to change …”
Section: Discussionmentioning
confidence: 99%
“…Census Bureau, 2012), while Filipinos have been one of the five largest groups of people immigrating into the U.S. every year since 1990 (Migration Policy Institute, 2010). Several previous studies have contended that culturally relevant smoking prevention and cessation interventions designed for A/PI should utilize strategies based on social network and social support theories (Burgess et al, 2014; Kim et al, 2015; Romero & Pulvers, 2013; Tsoh et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, a brief education intervention to mothers of sick children had a short-term effect in helping smoking fathers quit or reduce daily cigarette consumption (34). Initial acceptability and feasibility for a social network family-focused intervention has been demonstrated for Chinese and Vietnamese American male smokers in a recent study (35). Perception of a family norm toward cessation explained the effectiveness of a culturally tailored smoking cessation intervention for Korean American immigrant smokers that included coaching for family members on assisting smokers (36).…”
Section: Discussionmentioning
confidence: 99%